O sistema de metas de inflação e a crítica pós-keynesiana: uma aplicação para o Brasil - Silva, Fabiana de Lima (2009)
This work analyzes the Brazilian experience with the inflation targeting system from 1999 to 2007 under the post keynesian perspective. For this purpose, the New Consensus in Macroeconomics, which supports the proposition and management of this system, is described as well as the implications for emerging economies. The second chapter presents the understanding of the post Keynesian monetary policy and its criticism to the inflation targeting system. Finally, this work analyzes the inflation targeting system in Brazil, considering the post Keynesian critique. It concludes that the system of inflation targeting achieved relative success in its goal of stability with negative implications in terms of output growth of domestic economy. In addition, this system presents anti-growth bias that shows itself even more exacerbated, given the peculiarities of the Brazilian economy